2015
DOI: 10.1186/s12969-015-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nonbacterial osteomyelitis in children: a retrospective multicenter study

Abstract: BackgroundTo determine the clinical presentation, current treatment and outcome of children with nonbacterial inflammatory bone disease.MethodsRetrospective multicenter study of patients entered into the Swiss Pediatric Rheumatology Working Group registry with a diagnosis of chronic nonbacterial osteomyelitis (CNO) and synovitis acne pustulosis hyperostosis osteitis (SAPHO) syndrome. The charts were reviewed for informations about disease presentation, treatment, course and outcome.ResultsForty-one children (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 32 publications
(37 reference statements)
11
82
1
8
Order By: Relevance
“…The clinical course in both adults and children/adolescents is usually characterized by repeated episodes of active inflammation and remission but may present as single flares or have a chronic inflammatory pattern. 4,10,12,[26][27][28] Involvement of additional sites during the disease course is frequent, 7,10,11,16 but the disease progression, at least in adults, is usually minimal and slow, and SAPHO is not a particularly debilitating disorder. 9,11,12,29 Low-grade fever may be present during periods with disease activity, especially in children/adolescents, but other systemic manifestations are rare.…”
Section: Clinical Course Marked By Relapses and Remissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical course in both adults and children/adolescents is usually characterized by repeated episodes of active inflammation and remission but may present as single flares or have a chronic inflammatory pattern. 4,10,12,[26][27][28] Involvement of additional sites during the disease course is frequent, 7,10,11,16 but the disease progression, at least in adults, is usually minimal and slow, and SAPHO is not a particularly debilitating disorder. 9,11,12,29 Low-grade fever may be present during periods with disease activity, especially in children/adolescents, but other systemic manifestations are rare.…”
Section: Clinical Course Marked By Relapses and Remissionsmentioning
confidence: 99%
“…15,21,[33][34][35][36] WBMRI may visualize most of the osteoarticular changes of SAPHO/CRMO in one examination, especially when using coronal T1-weighted and STIR sequences in addition to axial STIR images of the whole body supplemented by sagittal sequences of the spine and/or dedicated MRI of inadequately visualized peripheral bone involvement. 28,[35][36][37] WBMRI is valuable for assessing total disease activity as well as for monitoring therapeutic response or the spontaneous course of the disease. 36 This radiation-free assessment of the entire body by WBMRI is particularly important in children/adolescents where repeated follow-up is often necessary because clinical remission does not necessarily mean radiologic remission.…”
Section: Choice Of Imaging Modalitymentioning
confidence: 99%
“…A prospective study of thirty-seven children showed good response to NSAIDs during the first 3–6 months of illness [9]. Other studies of CNO cohorts have documented the effectiveness of biologic and nonbiologic disease modifying antirheumatic drugs and bisphosphonates in treating CNO not controlled by NSAIDs [7, 8]. Understanding pediatric rheumatologists' practices in diagnosing and treating CNO would inform future refined diagnostic criteria and disease activity monitoring and enable development of standardized treatment regimens (consensus treatment plans) to allow for comparative effectiveness studies.…”
Section: Introductionmentioning
confidence: 99%
“…Because the clinical presentation may mimic infectious osteomyelitis or bone malignancy, it is important to perform a bone biopsy. Chronic nonbacterial osteomyelitis may also present with fever and arthritis (seen in this patient), skin lesions (e.g., acne, palmoplantar pustulosis, and psoriasis), and/or autoimmune disease such as Crohn's disease and ulcerative colitis . Our patient was started on daily loxoprofen, the mainstay treatment, which partially relieved her pain and improved laboratory indicators of inflammation.…”
mentioning
confidence: 81%